Soil Characteristics and Arbuscular Mycorrhizal Fungi from Different Pasture Types: A Case Study in the Western Black Sea Region, Turkey - Genç Lermi, Ayşe; Palta, Şahin; Palta, Şahin; Lermi, Ayşe Genç (Springer, 2022)
This research was conducted to compare the soil characteristics and arbuscular mycorrhizal fungi (AMF) spore density from different types of pastures. To this purpose, four different areas were selected including an artificial pasture (AP), a fertilized artificial pasture (FAP), a natural pasture (NP), and a fertilized natural pasture (FNP). From the spring period of 2008, urea has been used as a fertilizer at an annual rate of 5 kg/da. Different numbers of AMF spores were found in all soil samples taken from the artificial and natural pastures. The average numbers of AMF spores in 50 g of soil from the AP, the FAP, the NP, and the FNP were determined as 266.9, 125.3, 117.0, and 59.6, respectively. Both the number of AMF spores and the number of species were found to be lower in the fertilized pastures, and consequently, it was concluded that the urea fertilizer had reduced the number of AMF spores and species. Spores were identified according to their morphological characteristics. In all pastures, the study identified 25 different AMF species belonging to 11 genera from 7 families. Rhizoglomus aggregatum was classified as the dominant species in FNP soils. Acaulospora dilatata, A. laevis, Dentiscutata heterogama, Diversispora eburnea, Gigaspora albida, G. margarita, Claroideoglomus etunicatum, C. lamellosum, Funneliformis caledonium, Glomus hoi, Rhizoglomus clarum, R. irregulare, Sclerocystis sinuosa, and Ambispora gerdemannii were classified as rare species in all pastures. This study demonstrated a negative correlation between the AMF spore density and the soil organic carbon, total nitrogen, and available potassium.
Keywords: Community; Fertilization; Diversity; Litter; Land